ANALYSIS OF THE CONTRIBUTION OF PALM OIL CULTIVATIONS TO THE ECONOMY IN PASER DISTRICT OF EAST KALIMANTAN, INDONESIA - Solehuddin M.H.; Aziz Y.; Fajeri H. (Russian Journal of Agricultural and Socio-Economic Sciences)
Economic progress can be gauged by sustained increases in countrywide revenue or Gross Domestic Product (GDP), the growth of per capita revenue, and the attainment of overall economic well-being. Notably, the rural industry and cultivation industries play a significant role in driving the economic enhancement of Paser district. This research purposes to assess the role of oil palm cultivations in fostering the economic growth of Paser district while investigating the correlation between territory area and the economic participation of oil palm cultivations in the region. The research was carried out in Paser district by January to April 2023. The choice of this location was deliberate, given that Paser district hosts a diverse array of oil palm goods, including small-scale farmers cultivations, privately belonged estates, the oil palm handling industry, and various supporting industries. The information utilized in this research comprise secondary information origind by the Paser district Central Bureau of Statistics and the Paser District Office. The findings indicated a consistent annual rise in the participation of oil palm cultivations to the Gross Regional Domestic Product (GRDP) of Paser district. Additionally, the research revealed that variations in territory area did not have a significant impact on the participation of oil palm cultivations to the economic enhancement of Paser district.